Single‐Crystalline β‐Ga2O3 Homoepitaxy on a Near Van der Waals Surface of (100) Substrate - Tong Jiang; Hao Wang; Huaze Zhu; Junwei Cao; Xiaoqing Huo; Zhiqing Yang; Junshuai Li; Yaqing Ma; Shengnan Zhang; Xiang Xu; Wei Kong (Advanced Science)
Abstract Gallium oxide (Ga₂O₃) is a promising wide‐bandgap semiconductor for power devices, offering high breakdown voltage and low on‐resistance. Among its polymorphs, β‐Ga₂O₃ stands out due to the availability of high‐quality, large‐area single‐crystalline substrates, particularly on the (100) surface, grown via melt‐based bulk crystal growth. However, the low surface energy of β‐Ga₂O₃ (100), akin to 2D materials, presents challenges in homoepitaxy, including poor nucleation and twin formation, which hinder its practical application. This study demonstrates the successful homoepitaxial growth of single‐crystalline β‐Ga₂O₃ on (100) substrates using a van der Waals epitaxial approach. By introducing an excess surfactant metal in metal‐rich conditions at high temperature, a growth regime approximate thermal equilibrium is achieved, enhancing adatom diffusion and suppressing metastable twin phases. This adjustment enables the formation of well‐ordered, single‐crystalline nuclei and lateral stitching in a half‐layer‐by‐half‐layer growth mode, similar to 2D material growth. The result is twin‐free, atomically flat, single‐crystal thin films on on‐axis β‐Ga₂O₃ (100) substrates. These findings significantly improve the crystalline quality of epitaxial β‐Ga₂O₃ on (100) substrates, demonstrating their potential for scalable production of high‐performance, cost‐effective β‐Ga₂O₃‐based power devices, and advancing their feasibility for industrial applications.